Stage interaction multi-objective optimization of dynamic layout planning for irregular prefabricated construction site - Yao, Gang; Zhu, Mingtao; Yang, Yang; Lei, Ting; Zhou, Canwei; Men, Wulei (Journal of Building Engineering, 2025)
The storage and hoisting of prefabricated components have become critical issues in prefabricated construction. This highlights the need for a well-organized construction site layout planning (CSLP) to enhance both production efficiency and construction safety. Additionally, layout planning is subject to dynamic constraints such as site constraints, tower constraints, construction schedules, etc., which can change over time. The dynamic interactions between various construction stages, such as facility dismantling and removal, further influence CSLP. These two dynamic elements complicate the optimization of prefabricated CSLP, a subject that remains insufficiently explored. This paper addresses the dynamic prefabricated construction site layout planning (DP-CSLP) problem. It proposes a stage interaction DP-CSLP optimization method, encompassing a stage interaction DP-CSLP model and an innovative algorithm. The proposed model incorporates dynamic constraints, dynamic interactions and three-objective optimization. A multi-point simulation method is implemented to satisfy the precision hoisting requirements inherent in prefabricated construction, and a spatial boundary representation approach for irregular sites enhances the model's generalizability. To effectively tackle this model, a stage interaction constraint non-dominated sorting genetic algorithm II (SIC-NSGA-II) is proposed, which enables a multi-stage parallel search mechanism and provides strong global search capability and high computational efficiency. A case study is presented to illustrate the feasibility and effectiveness of the proposed method. The proposed method improves construction efficiency while reducing safety risk and operational cost, maximizing the benefits of prefabricated construction and providing a reference for future research. •An intelligent dynamic layout planning method for prefabricated construction is proposed.•A dynamic three-objective optimization model integrating inter-stage interactions is designed.•A multi-stage parallel search, fast-converging algorithm is designed.•A spatial boundary representation approach for irregular construction site is proposed.•The proposed planning method's efficiency is demonstrated through a practical case.